PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN KEMAMPUAN MENULIS PANTUN SISWA KELAS IV SD NEGERI 015 PENYAGUAN - Herlina '; Hendri Marhadi; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstact : Based on preliminary observations in SD Negeri 015 Penyaguan found problems in the class IV. So the impact on student learning outcomes are still relatively low and does not meet the standards KKM (75). Based on these problems the preferred solution is to apply the Cooperative Learning Model Make a Match, Cooperative Learning Model Make a Match is one type of cooperative learning model that consists of a group studying heterogeneous and each student work together, discussing about work and understand lessons are given and can enhance students' learning activities. The formulation of the problem of this study is Are Applying Cooperative Learning Model of Make a Match can improve the ability to write rhymes class IV of SD Negeri 015 Penyaguan. The purpose of this research is to improve the ability to write rhymes class IV SD Negeri 015 Penyaguan by applying Cooperative Learning Model of Make a Match. This research is a classroom action research with two cycles in four meetings. Subjects were students IV class totaling 30 people, male 15 and female 15 people. This research data collection techniques are observation, study and documentation of test results. The results showed the activities of teachers in the first cycle obtained a score of 18 on the first meeting with less cetegory and a score of 22 in the second meeting with the enough category. In the second cycle obtain a score of 26 in the first meeting with a good category and a score of 39 in the second meeting with a good category. Activities of students in the first cycle kuran obtain a score of 11 categories in the first meeting, and a score of 22 categories quite at the meeting 2. In the second cycle increased by a score of 28 categories of good and in the first meeting, and a score of 36 categories splendidly at the meeting to 2. Mastery learning classical I was 70% and the second cycle increased to 88%. The conclusion of this study is through the implementation of cooperative learning model make a match can improve the ability to write rhymes class IV SD Negeri 015 Penyaguan. Advice given that teachers should use cooperative learning model of make a match and varied media in the learning process. Keyword :  Cooperative learning model of make a match and improve the ability to write rhymes.